Leishmaniasis as a Manifestation of Immune Reconstitution Inflammatory Syndrome (IRIS) in HIV-Infected Patients: A Literature Review - Badaró, Roberto José da Silva (2014)
Universidade Federal da Bahia. Complexo Hospitalar Prof Edgard Santos. Salvador, BA, Brasil